Two series of luminescent phosphonate coordination polymers of lanthanides for sensing ketones and Fe3+ in water. (1st April 2022) - Zhang, Yu-Tong; Ruan, Jia-Xin; Ma, Dong-Sheng; Gao, Jin-Sheng; Liu, Yi-Fu; Yu, Ying-Hui
Graphical abstract: The synthesis of two series of lanthanide phosphonic acid coordination polymers by two ligands with different structures exhibited similar sensing ability toward iron ions and some ketone molecules, the sensing activity might be mainly relative to the available uncoordinated oxygen atoms in the CPs. Abstract: Two series of phosphonate coordination polymers (CPs) were designed and synthesized as probes for sensing certain pollutants in water. Six Ln phosphonate CPs, namely, Sm-HL1 (1), Pr-HL1(2), Nd-HL1(3), Sm-HL2(4), Pr-HL2(5), Nd-HL2(6) based on ( (2′-cyano-[1, 1′-biphenyl]-4-yl)methyl)phosphonic acid (HEtL1) 4′-((hydroxy(methoxy) phosphoryl)methyl)-[1, 1′-biphenyl]-2-carboxylic acid (H2 EtL2) were obtained by hydrothermal method. Their structures were confirmed and described through Single-crystal X-ray diffraction analysis, infrared spectra and thermogravimetric analysis. Their luminescence properties and sensing behaviors toward certain organic solvents and metal ions were detected and discussed. It was found that two types of CPs with different structures exhibited similar sensing ability toward iron ions and some ketone molecules, suggesting that the sensing activity might be mainly relative to the available uncoordinated oxygen atoms in the CPs rather than specific structures. The investigated CPs also showed good recyclability, guaranteeing its application as detecting probes.